2018
DOI: 10.2524/jtappij.72.1167
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Dissolving Pulp by Totally Chlorine-free Bleaching:Roles of Hardwood Syringyl and Guaiacyl Lignins

Abstract: Dissolving pulp was produced from four diff erent hardwoods by prehydrolysis-kraft cooking and totally chlorine-free (TCF) bleaching using oxygen (O) ,peroxymonosulfuric acid (P sa) ,and alkali extraction with hydrogen peroxide (E p) in an O-P sa-E p-P sa-E p sequence. The hardwood lignin structures were characterized by the nitrobenzene oxidation method, which provided syringaldehyde (S a) to vanillin (V a) molar ratios (S/ V ratios) of the lignin. Eucalyptus globulus wood had the highest S/V ratio of 5.81 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The results of chemical analysis indicated that A. crassicarpa wood consists of 41.1% glucan, 10.9% xylan, 31.5% lignin, and 2.1% acetone extractives (Table 1) . Compared with the contents of lignin and extractives for Eucalyptus globulus wood (27.6% and 0.6%, respectively) as stated in a previous report 20) , these were high, and nitrobenzene oxidation of A. crassicarpa wood showed that the lignin had a less syringyl and non-condensed structure. In addition, the xylan to glucan ratio of A. crassicarpa was lower than that of E. globulus (0.265 and 0.310, respectively) , and that is an advantage for dissolving pulp materials.…”
Section: Effects Of Saq Addition On Prehydrolysis Soda Cooking Of a. crassicarpamentioning
confidence: 44%
See 1 more Smart Citation
“…The results of chemical analysis indicated that A. crassicarpa wood consists of 41.1% glucan, 10.9% xylan, 31.5% lignin, and 2.1% acetone extractives (Table 1) . Compared with the contents of lignin and extractives for Eucalyptus globulus wood (27.6% and 0.6%, respectively) as stated in a previous report 20) , these were high, and nitrobenzene oxidation of A. crassicarpa wood showed that the lignin had a less syringyl and non-condensed structure. In addition, the xylan to glucan ratio of A. crassicarpa was lower than that of E. globulus (0.265 and 0.310, respectively) , and that is an advantage for dissolving pulp materials.…”
Section: Effects Of Saq Addition On Prehydrolysis Soda Cooking Of a. crassicarpamentioning
confidence: 44%
“…There was a tendency of increasing brightness based on increasing AA dosage for cooking (A) for all processes, and the soda cooking showed higher brightness than kraft cooking, except for one point of AA 20% without SAQ because of high kappa number (23.6) . When brightness was compared at the given kappa number (16)(17)(18)(19)(20) , soda cooking indicated higher brightness (3.8-3.9 points) than the kraft process (B) . A recent study on radiata pine 1) reported that the prehydrolysis process also made cellulose strength vulnerable, but significantly increased the brightness of the pulp.…”
Section: B Amentioning
confidence: 99%